Identification of hematopoietic progenitor cell donor characteristics predicting successful mobilization: results of an Italian multicenter study. Issue 8 (3rd March 2014) - Bertani, Giambattista; Santoleri, Luca; Martino, Massimo; Fedele, Roberta; Moscato, Tiziana; Marenco, Paola; Grillo, Giovanni; Zucchetti, Elisa; Lotesoriere, Ivana; Lando, Giuliana; Cesana, Clara; Cairoli, Roberto; et al.
<x xml:space="preserve">Abstract</x> Background Peripheral blood (PB) hematopoietic progenitor cells (HPC) collected by apheresis are the first‐choice source for allogeneic stem cell transplantation. The target HPC dose is usually considered to be 4 × 106 CD34+ cells/kg of the recipient, but higher doses are required in reduced‐intensity conditioning and haploidentical transplants. Thus, prolonged stimulation and repeated collections or failure to reach HPC target may occur, increasing risks for donors and recipients. We carried out a retrospective multicenter study on healthy donors, to identify donor variables which may correlate with HPC mobilization. Study Design and Methods HPC allogeneic donations from sibling and unrelated donors performed in two centers from 1995 to 2012 were analyzed. We defined a mobilization cutoff of 50 × 106 CD34+ cells/L and tested somatic variables, blood counts, and granulocyte–colony‐stimulating factor (G‐CSF) dose and molecular form. Results A total of 360 donors were analyzed (male, 201; female, 159; sibling, 348; unrelated, 12; median [range] age, 44.8 [13‐80] years). Median peak CD34+ in PB was 54.4 × 106/L (range, 5 × 106‐299 × 106). By multivariate analysis, we identified the following variables to correlate with good mobilization: 1) male sex (p < 0.0005); 2) younger age (p = 0.007); 3) higher baseline (premobilization) white blood cell (WBC) count (p < 0.0005); 4) higher G‐CSF dosage (p < 0.0005); and 5) use of lenograstim rather than filgrastim (p < 0.002). Conclusion In healthy donors it is possible to predict successful HPC mobilization by donor sex, age, WBC count, and G‐CSF form and dose. Furthermore, based on these data, it may be possible, at least in parental setting, to modulate G‐CSF dosage on the basis of donor characteristics.